FIXED OILS OF MEXICO III HABILLA DE SAN IGNACIO HURA POLYANDRA BAILL - MUNGUIA B, RICARDO; MILLARES, R; LLOYD, WR; GURLEY, NF (ARMOUR RESEARCH FOUNDATION, INTERNATIONAL DIVISION, CD. MEXICO, D F, MEX, 1949)
The physical and chemical characteristics of the oil of the seed of habilla de San Ignacio (Hura polyandra, Baill.) have been reported. The composition of the oil has been calculated. Â© 1949 American Oil Chemists' Society.
J AM OIL CHEM SOC
Keywords: FIXED, OILS, MEXICO, IGNACIO; QUIMICA; BIOQUIMICA; ACEITES FIJOS